2018
DOI: 10.1371/journal.pone.0205742
|View full text |Cite
|
Sign up to set email alerts
|

The calm during the storm: Snowfall events decrease the movement rates of grey wolves (Canis lupus)

Abstract: Mammalian predators encounter unique hunting challenges during the winter as snow increases the cost of locomotion and influences predator-prey interactions. Winter precipitation may also affect predators’ ability to detect and pursue prey. We investigated the effects of snowfall events on grey wolves (Canis lupus) in a boreal forest ecosystem in northeastern Alberta, Canada. We predicted that wolves would respond to snowfall events by reducing their travel speed and the time they spent travelling. Over the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Snow was only present during the first and last few weeks of our study (absent from May 5 until Sept. 15; [79]). The presence and depth of snow can influence both prey movements and their habitat selection [80,81] as well as the energetic costs of wolf movement [82]. Snow can be an impediment to movement in heavier-bodied herbivore prey due to higher foot loading [39,83], yet wolves were also less active and had lower movements during periods of deeper spring snow in the study area (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Snow was only present during the first and last few weeks of our study (absent from May 5 until Sept. 15; [79]). The presence and depth of snow can influence both prey movements and their habitat selection [80,81] as well as the energetic costs of wolf movement [82]. Snow can be an impediment to movement in heavier-bodied herbivore prey due to higher foot loading [39,83], yet wolves were also less active and had lower movements during periods of deeper spring snow in the study area (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…However, if the feet of these species sink to 60% of the brisket height, the energetic costs could span from 111% to 137% of that for a firm substrate, and beyond this point energy costs increase asymptotically ( Mattfeld 1974 ; Parker et al 1984 ; Fancy and White 1987 ). A 100% increase in the energy cost of locomotion has also been reported for coyote-sized dogs moving through 35 cm deep snow ( Droghini and Boutin 2018a )—77% of the chest height of a coyote ( Murray and Boutin 1991 ).…”
Section: Discussionmentioning
confidence: 79%
“…This contrasts to the only other data that exist for bipedal locomotion; studies of humans ( Heinonen et al 1959 ; Ramaswamy et al 1966 ) show a reduction in \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$U$\end{document} as sinking depth increases. Reductions in self-selected \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$U$\end{document} are observed in other species, albeit quadrupedal mammals, to keep the energetic cost of moving in deep snow acceptable ( Parker et al 1984 ; Fancy and White 1987 ; Crête and Larivière 2003 ; Droghini and Boutin 2018a ). These previous studies also report a positive association between the cost of locomotion and \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\bar{D}$\end{document} .…”
Section: Discussionmentioning
confidence: 99%
“…Our ptarmigan studies also highlighted the importance of understanding the influence substrate can have on locomotion [1]. Studies in extant animals have demonstrated that substrate can influence the neuromuscular control of locomotion to maintain stability [43][44][45] and can affect the energetic cost [46,47] and the speed [48] of locomotion. Furthermore, despite the obvious links between trackways and the ground, substrate is rarely considered when inferences into speed and gait are made from tracks.…”
mentioning
confidence: 82%